Is tax amnesty a good tax policy? : evidence from state tax amnesty programs in the United States - Luitel, Hari S., 1965- (Lexington Books, 2014)
Is a tax amnesty a good tax policy? To address this question, this book examines whether a typical state tax amnesty is likely to generate substantial short term tax revenues without a corresponding significant negative effect on long run tax compliance.